Liquidity Stress Tests for Investment Funds : A Practical Guide - Bouveret, Antoine (Washington, D.C. : International Monetary Fund, 2017)
This paper outlines a framework to perform liquidity stress tests for investment funds. Practical aspects related to the calibration of the redemption shock, the measurement of liquidity buffers and the assessment of the resilience of investment funds are discussed. The integration of liquidity stress tests with banking sector stress tests and possible bank-fund interlinkages are also covered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet